Sistem Informasi Akuntansi, Pengendalian Persediaan, dan Pertumbuhan UMKM Lombok Timur - Mardi, Mardi; Imtihan, Khairul; Zulkarnaen, Muhamad Fauzi (E-Jurnal Akuntansi; Vol 33 No 12 (2023)DO - 10.24843/EJA.2023.v33.i12.p13, 2023)
This research aims to examine the influence of the Accounting Information System (AIS) on inventory control and the growth of MSMEs in East Lombok Regency. The data analysis technique uses structural equation modeling-partial least squares ( SEM–PLS ) to analyze 53 research samples, namely MSMEs in East Lombok that use SIA in running their business, with a purposive sampling technique in determining the number of research samples. The research results show that SIA has a significant effect on inventory control, while SIA does not have a significant effect on the growth of MSMEs in East Lombok Regency, but SIA will have a significant effect on the growth of MSMEs if through inventory control or inventory control is able to intervene between SIA and the growth of MSMEs in East Lombok . This research can be used as a reference for MSME players to use SIA in running their business and for SIA software developers to pay more attention to the ease of system features created so that they can be used by all groups of MSME players. Keywords: AIS; Inventory Control; UMKM Growth